-2in(x)+in(y)=in(6)

Simple and best practice solution for -2in(x)+in(y)=in(6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2in(x)+in(y)=in(6) equation:


Simplifying
-2in(x) + in(y) = in(6)

Multiply in * x
-2inx + in(y) = in(6)

Multiply in * y
-2inx + iny = in(6)

Reorder the terms for easier multiplication:
-2inx + iny = 6in

Solving
-2inx + iny = 6in

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-6in' to each side of the equation.
-2inx + -6in + iny = 6in + -6in

Reorder the terms:
-6in + -2inx + iny = 6in + -6in

Combine like terms: 6in + -6in = 0
-6in + -2inx + iny = 0

Factor out the Greatest Common Factor (GCF), 'in'.
in(-6 + -2x + y) = 0

Subproblem 1

Set the factor 'in' equal to zero and attempt to solve: Simplifying in = 0 Solving in = 0 Move all terms containing i to the left, all other terms to the right. Simplifying in = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-6 + -2x + y)' equal to zero and attempt to solve: Simplifying -6 + -2x + y = 0 Solving -6 + -2x + y = 0 Move all terms containing i to the left, all other terms to the right. Add '6' to each side of the equation. -6 + -2x + 6 + y = 0 + 6 Reorder the terms: -6 + 6 + -2x + y = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -2x + y = 0 + 6 -2x + y = 0 + 6 Combine like terms: 0 + 6 = 6 -2x + y = 6 Add '2x' to each side of the equation. -2x + 2x + y = 6 + 2x Combine like terms: -2x + 2x = 0 0 + y = 6 + 2x y = 6 + 2x Add '-1y' to each side of the equation. y + -1y = 6 + 2x + -1y Combine like terms: y + -1y = 0 0 = 6 + 2x + -1y Simplifying 0 = 6 + 2x + -1y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 6x^2-11x-13=5(x^2-1)+3 | | 8+6x=7x-5 | | V+4=-5 | | Y=-16x+20x+5 | | 3X^(7/3)-6=0 | | 5x^3=85 | | (4y-8)(3y+7)=0 | | w=mxf+eforx | | z(z+7)=0 | | 12x6/6x3 | | -4q-(-7.3)=45.9 | | 1x+.12x=34000 | | (X6)6/x3 | | 12x-8=14x-34 | | -3.6+2z=13.6 | | -3x+5y=34whenx+3y-18 | | 8(p+1)-8= | | 31.9=-7+4m | | -3x+5y=34 | | -12+k=7.15 | | 2x+145=9x-9 | | y=x^3/x^2-1 | | 50x+60x=50x+80x | | -5=t/19-2 | | (6y^2-7y-5)(y-8)= | | 2x+15=-35 | | 4x-2(3x-1)=18 | | 5n+2=n+7 | | x^6=20 | | (3x*x)+6x=0 | | (3x*x)+12x-15=0 | | 3+4x-y=0 |

Equations solver categories